Kinetics of anodic reactions of molten potassium thiocyanate on platinum : Formation and growth of anodic film - Calandra, Alfredo J. (1971)
The film-growth process occurring on platinum anodes when molten potassium thiocyanate is electrolysed at 190°C has been investigated. The kinetics of the process has been studied by the application of different relaxation techniques. The film growth controls the rate of the process, and its mechanism comprises a surface diffusion process occurring after SCN−-ion oxidation. The film-thickening stage approaches a parabolic growth law. The faradaic rectification of the film is discussed in terms of its physicochemical properties and the actual site where anodic and cathodic reactions take place.